Introduction to the design and behavior of bolted joints : non-gasketed joints - Bickford, John H., 1926- (McGraw-Hill professional engineering. Mechanical engineering, 2008)
Provides information on the design and behavior of non-gasketed bolted joints, featuring a chapter on ways to control preload including the developments in ultrasonic and stretch control. This title includes sections on structural steel joins, airframe joints, vibration resistance fasteners, corrosion-resistant coatings, and other aspects.